2018
DOI: 10.1002/chir.22828
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical and vibrational spectroscopic study of genuine and counterfeit medicines containing tadalafil

Abstract: The production and distribution of counterfeit pharmaceuticals present a serious problem worldwide. This is true especially in case of phosphodiesterase type 5 inhibitors for treating erectile dysfunction, where consumers often prefer buying them anonymously from unverified sources. In this study, genuine and counterfeit Cialis® 20 mg tablets were analyzed by electronic circular dichroism, vibrational circular dichroism, and infrared spectroscopy. The characteristic spectral patterns were identified by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The results revealed that the counterfeit drugs contained a lower amount of tadalafil than that declared by the producer. 140…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the counterfeit drugs contained a lower amount of tadalafil than that declared by the producer. 140…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the counterfeit drugs contained a lower amount of tadalafil than that declared by the producer. 140 ECD and VCD were used to study (−)-brevianamide B (294) ( Figure 83) prepared by reduction and stereoselective oxidation from (+)-brevianamide A, isolated from Penicillium brevicompactum. The ECD bands are due to the (S) spiroindoxyl quaternary center which allowed confirming the AC.…”
Section: Nitrogenated Compoundsmentioning
confidence: 99%